2023
DOI: 10.1108/ijtc-03-2022-0069
|View full text |Cite
|
Sign up to set email alerts
|

Destination social responsibility drives destination brand loyalty: a case study of domestic tourists in Danang city, Vietnam

Abstract: Purpose This study aims to identify how perceived destination social responsibility (DSR) drives destination brand loyalty through a jointly and independently mediated mechanism of cognitive and affective components (e.g. tourist-destination identification, cognitive image, affective image and tourist satisfaction) and to examine the moderating role of individual-level collectivist values in linking perceived DSR and tourist behaviors. Design/methodology/approach An online survey is conducted to collect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Tourist satisfaction reflecting both customers' emotions is the critical aspect leading to the intention to revisit, the willingness to make more payments, and the spreading of positive WOM (Kahraman and Cifci, 2023;Mahmud et al, 2021;Tran et al, 2022). Findings from previous studies have confirmed that tourist satisfaction is a significant antecedent for destination brand loyalty (Ghafari et al, 2017;San Mart ın et al, 2019;Tran et al, 2023). As such, these hypotheses are proposed: H10.…”
Section: Jhti 72mentioning
confidence: 94%
“…Tourist satisfaction reflecting both customers' emotions is the critical aspect leading to the intention to revisit, the willingness to make more payments, and the spreading of positive WOM (Kahraman and Cifci, 2023;Mahmud et al, 2021;Tran et al, 2022). Findings from previous studies have confirmed that tourist satisfaction is a significant antecedent for destination brand loyalty (Ghafari et al, 2017;San Mart ın et al, 2019;Tran et al, 2023). As such, these hypotheses are proposed: H10.…”
Section: Jhti 72mentioning
confidence: 94%
“…This theory often relies on structural equation modeling to test the validity of the path by constructing a cognitive-emotional-intentional framework with corresponding variables. In tourism destination research, there is an influential relationship between tourists’ cognition, emotion, and destination brands based on loyalty ( Tran et al, 2023 ). CAC theory elucidates the interaction mechanisms between destination attachment formation and tourist psychology, revealing 3 psychological pathways ( Qu et al, 2021 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the study of factors influencing the online shopping behavior of Vietnamese consumers, the authors have identified five factors that impact online shopping behavior (Oke et al, 2016), including (1) perceived benefits, (2) perceived enjoyment, (3) website design, (4) psychological factors, and (5) perceived risk. When choosing a product or service, consumers usually on their rational thinking to maximize the value of their purchase based on the cost, consider the type of product or service they need, the reason for buying it, when to buy it, and where to buy it (Oke et al, 2016;Tran et al, 2023). Consumer behavior results from environmental factors that influence the buyer's consciousness, characteristics, and decisionmaking process, leading to certain shopping decisions (Oke et al, 2016).…”
Section: Perceived Values and Purchase Intentionmentioning
confidence: 99%